Analysis on the Effect of Sensor Views in Image Reconstruction Produced by Optical Tomography System Using Charge-Coupled Device - Jamaludin J.; Rahim, RA; Rahiman, MHF; Rohani, JM (IEEE-INST Electrical Electronics Engineers Inc, 2024)
Indexed by WOS/SCOPUS/ERA